Geological, geochemical and electrical constraints on the transient flow mechanism of the Dhor Barahi periodic spring in western Nepal - Perrier, Frederic; Gautam, Umesh; Chitrakar, Gyani Raja; Shrestha, Prithvi; Kafle, Basanta; Heritier, Thierry; Aupiais, Jean (Journal of Nepal Geological Society, 2002)
The Dhor Barahi spring in Tanahun district, Western Nepal, is characterised by intermittent periodic flow or unsteady continuous flow, depending on the time of the year. This behavior can be attributed to a siphon that can be cons trained by the local geology and water chemistry data. During periodic discharges, electrical signals are observed with an amplitude proportional to the water flow rate, as predicted by the electrokinetic effect, with a maximum coupling of -1.3±0.3 Vsm-3. The spatial structure of the surface potential leads to a qualitative descript ion of the electrical sources, also compatible with an electrokinetic mechanism, but additional contributions are possible. This study illustrates how combined geochemical and electrical measurements can provide access to the dynamics of groundwater circulation, with possible implications for the monitoring of hydrological, tectonic or volcanic processes.